THOUGHTS OF OUR GRANDFATHER IBN SINA IN THE DEVELOPMENT OF CHILDREN’S PHYSICAL ABILITIES: THOUGHTS OF OUR GRANDFATHER IBN SINA IN THE DEVELOPMENT OF CHILDREN’S PHYSICAL ABILITIES - Hasanov, anvar (Физическое воспитание, спорт и здоровье, 2022)
School students